2016
DOI: 10.1007/s11682-015-9503-4
|View full text |Cite
|
Sign up to set email alerts
|

FKBP5 modulates the hippocampal connectivity deficits in depression: a study in twins

Abstract: The hippocampus is a key modulator of stress responses underlying depressive behavior. While FKBP5 has been found associated with a large number of stress-related outcomes and hippocampal features, its potential role in modifying the hippocampal communication transfer mechanisms with other brain regions remains largely unexplored. The putative genetic or environmental roots of the association between depression and structural connectivity alterations of the hippocampus were evaluated combining diffusion weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…In general, it is currently hypothesized that depressed patients have increased basal FKBP51 levels [ 155 , 183 , 184 ] (although not observed in all populations [ 115 , 185 ]) that may be leading to a GR resistance [ 186 , 187 ]; alternatively, the basal promoter activity may be less relevant than the stress reactivity of the promoter that is shaped by genotype and epigenotype [ 6 ]. Moreover, the FKBP5 genotype has been reported to interact with the MDD diagnosis to predict structural neuroanatomical changes [ 116 , 188 , 189 , 190 ], as well as with prior lifetime trauma and/or stress to increase the risk for depression [ 191 , 192 , 193 , 194 ]. A recent meta-analysis performed with 26,582 subjects has also confirmed a significant association between both rs1360780 and rs3800373 with MDD [ 195 ].…”
Section: Functions Of Fkbp51mentioning
confidence: 99%
“…In general, it is currently hypothesized that depressed patients have increased basal FKBP51 levels [ 155 , 183 , 184 ] (although not observed in all populations [ 115 , 185 ]) that may be leading to a GR resistance [ 186 , 187 ]; alternatively, the basal promoter activity may be less relevant than the stress reactivity of the promoter that is shaped by genotype and epigenotype [ 6 ]. Moreover, the FKBP5 genotype has been reported to interact with the MDD diagnosis to predict structural neuroanatomical changes [ 116 , 188 , 189 , 190 ], as well as with prior lifetime trauma and/or stress to increase the risk for depression [ 191 , 192 , 193 , 194 ]. A recent meta-analysis performed with 26,582 subjects has also confirmed a significant association between both rs1360780 and rs3800373 with MDD [ 195 ].…”
Section: Functions Of Fkbp51mentioning
confidence: 99%
“…An important modulator of these interactions is FKBP5 (Hoeijmakers et al, 2014; Schmidt et al, 2015), which codes for the FK506-binding protein 51 (FKBP51) and has emerged as a promising drug target for its involvement in numerous neuropsychiatric disorders, including PTSD (Binder et al, 2004, 2008; Binder, 2009; Binder et al, 2010; Lavebratt et al, 2010; Ellsworth et al, 2013; Klengel et al, 2013; Alemany et al, 2016; Stamm et al, 2016; Yehuda et al, 2016). Notably, new studies show a strong relationship between the FKBP5 gene and hippocampal volumes and connectivity (Zobel et al, 2010; Fani et al, 2013; Córdova-Palomera et al, 2016). Thus, FKBP51 may play a role in predisposing the brain to traumatic stress by virtue of regulating the structural integrity of the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies have further conducted controlled experiments and concluded that the correlation between Tardive Depression and hippocampal volume was stronger than that of early-onset depression, and the smaller hippocampus volume is associated with higher levels of cortisol [16]. Besides, stress-related FKBP5 was related to hippocampal characteristics [17]. After analyzing a sample of a certain number of identical twins, it was concluded that the right hippocampus of patients with depression has decreased connection strength and increased network centrality, thereby revealing the manner in which the hippocampus communicates with the rest of the brain in those who are depressed.…”
Section: Hippocampusmentioning
confidence: 99%